Bonjour, je n'arrive pas à développer A=(2x-3)^2-(4x+5)(6-2x)

Merci d'avance <3​


Sagot :

Réponse :

Bonjour

Explications étape par étape :

A=(2x-3)^2-(4x+5)(6-2x)

A= (2x)²-2×2x×3+3² - ( 4x×6+4x×(-2x)+5×6+5×(-2x))

A= 4x²-12x+9 -( 24x-8x²+30-10x)

A= 4x²-12x+9-24x+8x²-30+10x

A= 4x²+8x²+10x-12x-24x+9-30

A= 12x² -26x -21

Bonjour,

Simplifier :

A = (2x-3)²-(4x+5)(6-2x)

↳ Identité remarquable : (a-b)² = a²-2ab+b²

A = 4x²-12x+9-(4x+5)(6-2x)

A = 4x²-12x+9-(24x-8x²+30-10x)

A = 4x²-12x+9-(14x-8x²+30)

A = 4x²-12x+9-14x+8x²-30

A = 12x²-12x+9-14x-30

A = 12x²-26x+9-30

A = 12x²-26x-21

Bonne journée.